Is transcranial sonography useful for diagnosing Parkinson’s disease in clinical practice? - Talyta Cortez Grippe; Nasser Allam; Pedro Renato de Paula Brandão; Danilo Assis Pereira; Francisco Eduardo Costa Cardoso; Ana Carolina Rodrigues Aguilar; Iruena Moraes Kessler (Arquivos de Neuro-Psiquiatria)
ABSTRACT Transcranial sonography (TCS) is an emerging ancillary examination for diagnosing Parkinson’s disease (PD). Objective To evaluate TCS features in patients with PD and its mimics, and establish their accuracy in predicting the final clinical diagnosis after follow-up. Methods We retrospectively studied 85 patients with an initial clinical suspicion of PD, atypical parkinsonism or essential tremor, all of whom underwent TCS. Two specialists reviewed the follow-up clinical visit records and determined the final clinical diagnosis. The accuracy analysis of the TCS was determined using Bayesian statistical methods. Results The finding of substantia nigra hyperechogenicity (> 20 mm2) showed high sensitivity (93.4%) and specificity (86.6%). The positive likelihood ratio showed 6.93-fold greater odds for diagnosing PD than an alternative condition when this finding was present. Conclusions This study revealed the practical usefulness of TCS in differentiating PD from its prevalent mimics when the clinical diagnosis was initially unclear.